Electronic Medical Records (EMR) Using a Software as a Service (SaaS) with a Single Identity Number at the Polije Polyclinic - Pratama, Mudafiq Riyan; Alfiansyah, Gamasiano; Swari, Selvia Juwita; Wardana, Aulia Arif (Indonesian Journal Publisher, 2023)
Manual management of medical records at the Polije Polyclinic causes long data retrieval time, misfiling, and requiring a lot of spaces for storage, thus hampering health services. Electronic Medical Records (EMR) are one type of medical record management that can be used to solve the issue. EMR is built based on Software as a Service (SaaS) which enables it to be used by all healthcare providers with minimal infrastructure and optimal data integration. The application used a single identity number for each patient, and it caused less redundancy in patient registration data. Developed using the Waterfall method, it was processed at several stages: analysis, design, implementation, testing, deployment, and maintenance. The EMR system had some features: recording history, diagnosis, and therapy. In the diagnosis section, the system had a disease code related to ICD-10. It can be concluded that the Electronic Medical Record (EMR) is ready to be implemented in the POLIJE polyclinic. The implementation of EMR is important to reinforce the Regulation of the Indonesian Minister of Health Number 24 of 2022 concerning Medical Records.